Novel bio based resins from blends of functionalized palm oil and unsaturated polyester resin - Mustapha, Siti Noor Hidayah (2013)
Unsaturated polyester resin material containing epoxidised palm oil is a new alternative for bio-based thermoset material. Unsaturated polyester resin blends with epoxidised palm oil weresynthesised using benzoyl peroxide as an initiator. Unsaturated polyester resin blends withvarious content of epoxidised palm oil (10, 20 and 30 wt-%) were studied. The samples werecured in an oven at 100°C for 2 hours followed by post-curing at 160°C for another 2 hours. Theeffects of epoxidised palm oil loadings in unsaturated polyester resin on the thermo-physicalproperties and izod impact strength were studied. The findings reveal that the storage modulusof unsaturated polyester resin/epoxidised palm oil bioresin decreased slightly by the addition ofepoxidised palm oil. At 20 wt-% of epoxidised palm oil loadings, the glass transition temperature(Tg) decreased by±5°C and the storage modulus decreased by about 20% from the original unsaturated polyester resin.